El intercambio de dones en el mundo griego: reciprocidad, imprecisión, equivalencia y desequilibrio - Domingo Gygax, Marc (Gerión. Revista de Historia Antigua, 2008)
This paper analyzes some basic principles and characteristics of gift-exchange in the Greek world. Two divergent aspects of the obligation to reciprocate gifts with counter-gifts will be explored: on the one hand, the recipient’s tendency to try to cancel the obligation with equivalent counter-gifts and, on the other, the necessity of some imprecision about the degree of equivalence so as to keep the gift-exchange within the limits of reciprocal generosity and so that it not become an exchange of commodities. Some consequences of this paradox are examined: the difficulty in balancing the relationship between givers and recipients in order that neither party feels in debt, and the formation of chains of gifts and counter gifts.